Before you turn the page: Connecting the parallel worlds of El Sistema and critical research. Issue 1 (July 2016) - Baker, Geoff
This article consists of a series of reflections on research on El Sistema and the reception of the first (and to date only) academic book on the program. It underlines the uncertainty of the international Sistema sphere in the face of the information that is emerging about the Venezuelan program, and proposes various reasons for taking that information seriously and beginning an open and honest debate about El Sistema's problems and the positions that those who have been inspired by the program might take with regard to them, rather than continuing with blind eulogy or turning the page. The second part of the article considers the future of academic research on El Sistema, focusing on the differences between qualitative and quantitative studies, and between academic research and consultancy evaluations. It concludes with some reflections on the possibilities for closing the gap between the parallel worlds of El Sistema and critical research.